Dominant Variables That Affect The Level of Profitability in Sharia Banks and Conventional Banks - Irawati Junaeni (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
This study aims to analyze the dominant factors that affect profitability in the Sharia Commercial Bank and Conventional Bank Indonesia Year 2009-2014. The sample used in this study is 7 Sharia Commercial Banks and 10 Conventional Commercial Banks in Indonesia. The technic sample used in this study by purposive sampling method. This research uses panel data regression methods and estimation model used is a Random Effect Model. The result of research on sharia bank of internal factors concludes that BOPO variable has a significant influence on return on asset (ROA) and from external factors of BI Rate significant effect on return on asset (ROA). While conventional banks of internal factors conclude that BOPO and NPL variable have significant influence to return on asset (ROA) and from external factor conclude that BI Rate has a significant effect to return on asset ROA). In this research, BOPO variable has a more dominant influence on  ROA than other variables.